Differences in von Willebrand factor function in type 2A von Willebrand disease and left ventricular assist device‐induced acquired von Willebrand syndrome. Issue 4 (8th October 2018) - Deconinck, Shannen; Tersteeg, Claudia; Bailleul, Els; Delrue, Leen; Vandeputte, Nele; Pareyn, Inge; Itzhar‐Baikian, Nathalie; Deckmyn, Hans; De Meyer, Simon F.; Vanderheyden, Marc; Vanhoorelbeke, Karen
Abstract: Background: Patients with von Willebrand disease (VWD) type 2A or acquired von Willebrand syndrome (aVWS) as a consequence of implantation of left ventricular assist devices (LVAD) are both characterized by a loss of von Willebrand factor (VWF) function. Loss of VWF function is however more severe in VWD type 2A than in LVAD patients. Objectives: To compare VWF function in patients with VWD type 2A and LVAD‐induced aVWS to highlight the differences in VWF activity and to stress the importance of VWF multimer analysis for correct diagnosis of aVWS in LVAD patients. Patients/Methods: Plasma samples from nine VWD type 2A, nine LVAD patients, and 20 healthy donors (HD) were analyzed for VWF function (VWF:CB/VWF:Ag and VWF:RCo/VWF:Ag) and loss of high molecular weight (HMW) VWF multimers. Results: A severely impaired VWF function was indeed confirmed in all VWD 2A patients. HMW VWF multimers were severely reduced compared to HD (0% [0, 12.29] vs 34.19% [31.68, 38.88] for HD, P  <   0.001) and this loss was reflected by VWF:CB/VWF:Ag and VWF:RCo/VWF:Ag ratios <0.7. In contrast, VWF function was less affected in LVAD patients. Although HMW VWF multimers were reduced in all patients (20.31% [15.84, 21.71], vs 34.19% [31.68, 38.88] for HD, P  <   0.001), six out of nine LVAD patients had normal VWF:CB/VWF:Ag or VWF:RCo/VWF:Ag ratios (>0.7). Conclusions: VWF:CB/VWF:Ag or VWF:RCo/VWF:Ag analysis allows detection of impaired VWF function in VWD type 2A but not always in LVAD‐induced aVWS patients. In contrast, VWF multimeric analysis allows detection of the loss of HMW VWF multimers in both groups of patients. Hence, performing VWF multimer analysis is crucial to detect aVWS in LVAD patients.